Calculation of Modes and Power Losses in 0.38 kV Electrical Networks in View of Repeated Earth Connection of Zero Wire - M. I. Fursanov; A. A. Zalatoi; V. V. Makarevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A methodology has been developed to take account of repeated earth connection of a zero wire while making calculation of modes and losses in 0.38 kV and using method of nodal potentials that permits to refine operating conditions of a zero wire. It has been shown that an account of a repeated earth connection of a zero wire exerts an influence on parameters of a mode and power loss in the 0.38 kV network and in this case an influencing force is in direct proportion to unsymmetry degrees of load phase currents and is in inverse proportion to resistance of earthing devices and rods